Outcomes of follow-up care after an emergency department visit among pediatric asthmatics in the military health system. (13th September 2016) - Smiley, Michael; Sicignano, Nicholas; Rush, Toni; Lee, Rees; Allen, Elizabeth
Abstract: Background and Objectives : Asthma exacerbations frequently trigger emergency department (ED) visits. Guidelines recommend timely follow-up after an ED visit for asthma, however, other studies have questioned the quality of follow-up care and their effect on subsequent ED utilization. We evaluated follow-up care on asthma outcomes in pediatric asthmatics enrolled in the Military Health System (MHS) after an ED visit for asthma. Methods : This retrospective study utilized MHS data to evaluate 2–17-year-old persistent asthmatics with an ED visit for asthma between 2010–2012. Demographics, medication dispensing, and subsequent asthma related ED and hospital utilization were compared between those with or without a 28-day follow-up appointment. Results : 10, 460 of 88, 837 persistent asthmatics met inclusion criteria for an asthma ED visit. 4, 964 (47.5%) had ≥ 1 follow-up visit. In the 29–365 days after their ED visit, 21.1% of the follow-up cohort required an ED re-visit compared to 24.0% of the patients without follow-up. Follow-up care was associated with a reduction in ED re-visits (adjusted hazard ratio 0.86; 95% confidence interval 0.79, 0.93). Controller medications were dispensed to 76.0% of the follow-up cohort within 90 days of their ED visit compared to 49.7% in the group without follow-up. Conclusions : Despite universal access to healthcare, less than half of pediatric MHS asthma patients had follow-up within 28 days of an ED visit. Those with follow-up were more likely to fill a controller medication within 90 days post-ED visit, and less likely to have an asthma ED re-visit in the subsequent year.